2012
DOI: 10.1371/journal.pone.0040217
|View full text |Cite|
|
Sign up to set email alerts
|

Phenotypic Characterization of Prostate Cancer LNCaP Cells Cultured within a Bioengineered Microenvironment

Abstract: Biophysical and biochemical properties of the microenvironment regulate cellular responses such as growth, differentiation, morphogenesis and migration in normal and cancer cells. Since two-dimensional (2D) cultures lack the essential characteristics of the native cellular microenvironment, three-dimensional (3D) cultures have been developed to better mimic the natural extracellular matrix. To date, 3D culture systems have relied mostly on collagen and Matrigel™ hydrogels, allowing only limited control over ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 88 publications
6
74
0
Order By: Relevance
“…S4 ). [28] In summary, androgen responsiveness and AR signaling were in general not affected by growing LNCaP cells on PLO, PLL or FN substrates. Table 1 summarizes the effects of the different coating substrates on androgen responsiveness and on other cellular parameters investigated in this study.…”
Section: Resultsmentioning
confidence: 87%
“…S4 ). [28] In summary, androgen responsiveness and AR signaling were in general not affected by growing LNCaP cells on PLO, PLL or FN substrates. Table 1 summarizes the effects of the different coating substrates on androgen responsiveness and on other cellular parameters investigated in this study.…”
Section: Resultsmentioning
confidence: 87%
“…Work by Lang et al seems to indicate that Matrigel™ induces morphological changes that may be indicative of gene expression profile changes [107]. More recent studies have indicated more finely tuned materials such as PEG hydrogels, containing arginine-glycine-aspartate (RGD) and matrix metalloproteinase (MMP) cleavage sites, provide a micro-environment that better recapitulates native tissue environment [108]. This consideration should be made particularly if hormone sensitivity or drug discovery studies are being conducted.…”
Section: In Vivo Model Systemsmentioning
confidence: 99%
“…Recently, exome sequencing of LNCaP cells revealed significant genetic variation and a degree of genetic instability that should be considered when working with this cell line (Spans et al 2012). In addition, AR signaling and androgen responsiveness of LNCaPs appear to be sensitive to serial passaging and culture conditions (Karan et al 2001, Sieh et al 2012. For example, when grown in 3D hydrogels with Arg-Gly-Asp (RGD) motifs (common recognition sites in extracellular matrix (ECM) proteins), LNCaP cells formed tumor-like structures and exhibited different kinetics of androgeninduced AR turnover and AR nuclear translocation with higher basal expression levels of ARGs, a finding also observed upon culture of LNCaPs on bone ECM (Robbins et al 1996, Sieh et al 2012.…”
Section: Cell Lines Established Directly From Pca Patient Tissuesmentioning
confidence: 99%